High-Order Parity Improves the Perinatal Outcome of Twin Deliveries - Kashani-Ligumsky, Lior; Cohen, Ronnie; Many, Ariel; Elmalech, Avshalom; Neiger, Ran; Lopian, Miriam (American Journal of Perinatology, 2023)
Objective Twin gestations are associated with an increased risk of obstetric and perinatal complications. We studied the association between parity and the rate of maternal and neonatal complications in twins deliveries.Study Design We performed a retrospective analysis of a cohort of twin gestations delivered between 2012 and 2018. Inclusion criteria consisted of twin gestation with two nonanomalous live fetuses at ≥24 weeks' gestation and no contraindications to vaginal delivery. Women were divided into three groups based on parity: primiparas, multiparas (parity of 1–4), and grand multiparas (parity ≥5). Demographic data were collected from electronic patient records and included maternal age, parity, gestational age at delivery, need for induction of labor, and neonatal birth weight. The primary outcome was mode of delivery. Secondary outcomes were maternal and fetal complications.Results The study population included 555 twin gestations. One hundred and three were primiparas, 312 were multiparas, and 140 were grand multiparas. Sixty-seven (65%) primiparas delivered the first twin vaginally, as did 294 (94%) multiparas and 133 (95%) grand multiparas (p <0.05). Thirteen (2.3%) women required delivery of the second twin by cesarean section. Among those who delivered both twins vaginally, there was no significant difference in the average time interval between the delivery of the first and the second twins between the groups. The need for transfusion of blood products was higher in the primiparous group compared with the other two groups (11.6 vs. 2.5 and 2.8%, p < 0.05). The rate of adverse maternal composite outcomes was higher among primiparous women compared with multiparous and grand multiparous (12.6, 3.2, and 2.8%, respectively, p < 0.05). The gestational age at delivery was earlier in the primiparous group compared with the other two groups, and the rate of preterm labor at <34 weeks' gestation was higher among the primiparas. The rate of second twin's 5-minute Apgar's score <7 and the composite adverse neonatal outcome among the primiparous group were significantly higher than the multiparous and grand multiparous groups.Conclusion Our study demonstrates that there is an association between high-parity and good obstetric outcomes in twin pregnancies; high parity seems to serve as a protective, rather than a risk factor for adverse maternal and neonatal outcomes.Key Points
Keywords: twin gestation; pregnancy; high-order parity; cesarean delivery